Does Native Combined Anteversion Influence Pain Onset in Patients With Dysplastic Hips?. Issue 12 (December 2015) - Kohno, Yusuke; Nakashima, Yasuharu; Akiyama, Mio; Fujii, Masanori; Iwamoto, Yukihide
Abstract: Background: Combined anteversion is the sum of femoral and acetabular anteversion and represents their morphological relationship in the axial plane. Few studies have investigated the native combined anteversion in patients with symptomatic dysplastic hips. Questions/purposes: We hypothesized the following: (1) dysplastic hips have two distinct populations, which differ from each other and from normal hips in their combined anteversion; and (2) these populations differ clinically in terms of correlation between age of onset of symptoms and amount of anteversion. Methods: We measured radiographic parameters by CT of 100 dysplastic hips in 76 patients who were symptomatic enough to undergo periacetabular osteotomy and of 50 normal hips in 44 patients who had CT scans as part of preparation for computer‐navigated TKAs; these patients had no visible hip arthritis or dysplasia and no hip symptoms. Dysplastic hips were divided into the anteversion (83 hips) and retroversion groups (17 hips) based on acetabular version. Age at pain onset was determined from their medical charts. Results: Combined anteversion in the anteversion group was greater than that in the retroversion and control groups: 47° ± 12°, 30° ± 16°, and 36° ± 9°, respectively. In the anteversion group, combined anteversion (r = −0.49; 95% confidence interval [CI], −0.66 to −0.27; p < 0.001) and femoral anteversion (r = −0.41; 95% CI, −0.60 to −0.19; p < 0.001) were associated with an earlier age at pain onset; however, no such relationships were observed in the retroversion group. After controlling for relevant potential confounding variables, we found that combined anteversion (hazard ratio [HR], 1.04; 95% CI, 1.01‐1.07; p = 0.006) and Sharp angle (HR, 1.10; 95% CI, 1.02‐1.17; p = 0.008) were associated with an earlier age of pain onset in the anteversion group. Conclusions: These results suggest that not only lateral coverage of the femoral head, but also axial joint morphology is important for the development of pain in the anteversion group. Optimal combined anteversion should be considered during periacetabular osteotomy. Level of Evidence: Level IV, prognostic study.